IDENTIFICATION AND PHYLOGENY ANALYSIS OF TWO NEW Fusarium SPECIES CAUSING DRY ROT ON POTATO TUBERS IN IRAQ - RAMADAN , SHLER MOHAMMED; HALEEM, RAED ABDUL JABBAR (Journal of Duhok University, 2023)
Fusarium equiseti and Fusarium oxysporum are the two Fusarium species most frequently linked to Fusarium dry rot of potatoes in Duhok province, Kurdistan region, Iraq. First symptoms on the surface of the infected tuber were a brownish to black lesion. These lesions eventually become sunken as the damaged tissue dries out, forming a large hollow cavity that usually filled with visual colored fungal mycelium. F. oxysporum was the most pathogenic species discovered on potato tubers (Arizona cv.), and it produced lesions that were 23.86 mm deep and 21 mm wide. F. equiseti was less aggressive, leaving wounds measuring 12.86 mm in depth and 8.14 mm in width.F. oxysporum   produced white to pale pinkish colories when grown on PDA in the darck at 25 °C and produced dense microconidia in false heads with short monophialides. While F. equiseli  on PDA pure culture at 25 °C ,characterized with white colonies turned to beach orange in color, ,Microconidia were not formed, Many macroconidia had prominent foot cells and tapering, elongated apical cells. They were also curved, hyaline, and 2–5 septate.Maximum Parsimony analysis on the Internal Transcribed Spacer (ITS) supports the monophyletic relationship between Iraqi strains of Fusarium oxysporum (B11T2, GenBank: OP379284) and Fusarium equiseti (E13T4, GenBank: OP494711). With 99% maximum parsimony, Fusarium oxysporum was placed in the same clade as strains BMS, EPOOL, and voucher RAB1113317 (MP). While Fusarium equiseti has been placed in the same clade as strains 18, A577, 48, and MK7IA-FE with 95% MP.For the first time, both Fusarium species have been molecularly identified to be the main contributors to the dry rot that Fusarium causes on potato tubers in Iraq